Evaluation of olive oil as a separating medium and its effect on some physical properties of processed acrylic resin denture base (A comparative study). Part one - Al-Taie, Akhlas Z; Al-Nakkash, Widad A; Salman, Farhan D (Journal of Baghdad College of Dentistry, 2015)
Back ground: During acrylic resin processing, the mold must be separated from the surface of the gypsum to prevent liquid resin from penetrating into the gypsum, and water from the gypsum seeping into the acrylic resin. For many years, tin foil was the most acceptable separating medium, and because it’s difficult to apply, a tin-foil substitute is used. In this study, olive oil is used as an alternative to tin foil separating medium for first time, so the aim of the study was to evaluate its effect as a separating medium on some physical properties such as (surface roughness, water sorption and solubility) of acrylic resins denture base comparing it with those processed using tin-foil and tin foil substitute such as (cold mold seal) separating medium. Materials and methods: One hundred forty two acrylic resins samples (124) were prepared falling in two main groups: [heat and cold-cured acrylic denture base resins ], for each group three types of separating medium were used and five tests (10 samples) for each test were carried out , and (4) samples for the chemical composition. Result: From the result obtained, tin foil is one of the most satisfactory separating media in getting the best properties when using it as a separating medium, while, a statistically no-significant difference have been noticed between olive oil and cold-mold seal samples concerning physical and mechanical properties of tested groups. Infrared spectroscopy analysis showed that, no changes were found in the chemical composition of both heat and cold-cured acrylic resins denture base after using olive oil as a separating medium. Conclusion: Lastly, from the results of this study it may be concluded, that olive oil may be used as a substitute for tin foil and cold â€“ mold seal separating medium in processing both heat and cold â€“ cure acrylic resin denture base.